Inadequate Housing Among Families Under Investigation for Child Abuse and Neglect: Prevalence from a National Probability Sample. Issue 1 (24th May 2013) - Fowler, Patrick J.; Henry, David B.; Schoeny, Michael; Landsverk, John; Chavira, Dina; Taylor, Jeremy J.
Abstract: This study aimed to estimate the prevalence of inadequate housing that threaten out‐of‐home placement among families under investigation by child welfare. Data came from the National Survey of Child and Adolescent Well‐Being, a nationally representative longitudinal survey of child welfare‐involved families. Child protective services caseworkers as well as caregivers provided information on families whose child remained in the home after initial investigation ( N = 3, 867). Multilevel latent class analyses tested the presence of inadequately housed subgroups using 4 housing problem indicators at baseline. Logistic regressions assessed convergent and predictive validity. A two class latent solution best fit the data. Findings indicated that inadequate housing contributed to risk for out‐of‐home placement in approximately 16 % of intact families under investigation by child protective services. These families were 4 times more likely to need housing services 12 months later. Federal legislation emphasizes integration of social services as necessary to end homelessness. This study demonstrates overlap across public agencies. Enhanced coordination of child welfare and housing services facilitates interventions to prevent and mitigate homelessness.